Suspending classes without stopping learning: China's education emergency management policy in the COVID-19 outbreak - Wunong Zhang; Yuxin Wang; Lili Yang; Chuanyi Wang (Journal of Risk and Financial Management, 2020)
Against the backdrop of the COVID-19 outbreak, an emergency policy initiative called "Suspending Classes Without Stopping Learning" was launched by the Chinese government to continue teaching activities as schools across the country were closed to contain the virus. However, there is ambiguity and disagreement about what to teach, how to teach, the workload of teachers and students, the teaching environment, and the implications for education equity. Possible difficulties that the policy faces include: the weakness of the online teaching infrastructure, the inexperience of teachers (including unequal learning outcomes caused by teachers' varied experience), the information gap, the complex environment at home, and so forth. To tackle the problems, we suggest that the government needs to further promote the construction of the educational information superhighway, consider equipping teachers and students with standardized home-based teaching/learning equipment, conduct online teacher training, include the development of massive online education in the national strategic plan, and support academic research into online education, especially education to help students with online learning difficulties.
Keywords: 330; COVID-19; China; school; emergency management; emergency policy; Suspending Classes Without Stopping Learning; online teaching